STRATEGI MITIGASI KENAKALAN REMAJA DI MTS JAMIYATUL AULAD PALABUHAN RATU KABUPATEN SUKABUMI - Elisya, Ovi Tamayanti; Hardian, Dafyar Eliadi; Latuconsina, Hudaya (Perspektif : Jurnal Ilmu Administrasi, 2025)
violates societal norms and laws, committed during adolescence or during the transition from childhood to adulthood. Deviant behavior by adolescents violates criminal law norms and is a common problem for adolescents, both within the family, school, and community. If not handled properly, juvenile delinquency can escalate into criminal behavior and lead to imprisonment. This study aims to analyze in depth how madrasah principals and stakeholders attempt to develop strategies to mitigate juvenile delinquency. It also explores the principals' strategies for hindering the process of mitigating juvenile delinquency during its implementation. The method used was a descriptive qualitative approach, with data collection techniques including in-depth interviews, participant observation, and documentation. Informants included madrasah principals, student affairs officers, guidance counselors, homeroom teachers, police officers, and parents. The research results indicate that this mitigation strategy is addressed through the implementation of a management information system with communication media, collaboration with government agencies and guidance from the school, development of standard operating procedures (SOPs) with warning letters and disciplinary provisions, and supervision by school stakeholders. This research recommends that the principal and school stakeholders continuously strive to work together to achieve established goals. Keywords: Management Information System, Mitigation Strategy, SOPs, and Supervision.